2021
DOI: 10.1007/s40744-020-00273-w
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies in Inflammatory and Autoimmune Rheumatic and Musculoskeletal Diseases Beyond Lupus: A Systematic Review of the Available Evidence

Abstract: Background The diagnosis of antiphospholipid syndrome (APS) requires the presence of thrombosis and/or recurrent miscarriages along with one or more anti-phospholipid antibodies (aPL). The role of aPL has been largely investigated in systemic lupus erythematosus (SLE) with minimal data on other autoimmune rheumatic diseases. In this review, we aim to assess the prevalence of aPL in patients with inflammatory and autoimmune rheumatic and musculoskeletal diseases (RMDs) other than SLE, and their ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This finding is not surprising, since the association of these autoantibodies with thromboembolism has been found in other inflammatory and autoimmune rheumatic diseases. 72 The mean prevalence of anti-phospholipid autoantibodies in RA has been found at 28% and the median was 22%. 73 In a recently published systematic review, authors suggested that there are not enough data to support routine screening for antiphospholipid antibodies in RA, with a possible exception for pregnancy planning and thrombosis in the context a rheumatic disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is not surprising, since the association of these autoantibodies with thromboembolism has been found in other inflammatory and autoimmune rheumatic diseases. 72 The mean prevalence of anti-phospholipid autoantibodies in RA has been found at 28% and the median was 22%. 73 In a recently published systematic review, authors suggested that there are not enough data to support routine screening for antiphospholipid antibodies in RA, with a possible exception for pregnancy planning and thrombosis in the context a rheumatic disease.…”
Section: Resultsmentioning
confidence: 99%
“… 73 In a recently published systematic review, authors suggested that there are not enough data to support routine screening for antiphospholipid antibodies in RA, with a possible exception for pregnancy planning and thrombosis in the context a rheumatic disease. 72 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the various complications and effects of rheumatic disorders on the health system of developing countries, the International Union of Rheumatology Association together with the community-oriented World Health Organization (WHO) has proposed a program to control rheumatic diseases, with the aim of identifying, preventing and controlling them. Reliable epidemiological studies have been considered necessary and important in the study of the prevalence of rheumatic disorders in different countries, especially developing countries [8,13]. However, differences in prevalence or diseases in different geographical areas have always been of interest to researchers in the field of health and medicine due to genetic, geographical and cultural issues.…”
Section: Introductionmentioning
confidence: 99%
“…According to a systematic review by El Hasbani G. et al (2021), antiphospholipid antibodies can be detected on average in 14% of patients with inflammatory and autoimmune rheumatic and mus culo skeletal diseases (in addition to systemic lupus erythematosus) [6]. According to Olech E. et al, the incidence of antiphospholipid antibodies (aPL) in patients with RA is 28% (median -22%) [13] being slightly lower in systemic scleroderma (> 30%) [6].…”
Section: Introductionmentioning
confidence: 99%